Towards a post-traumatic subtype of obsessive-compulsive disorder - Fontenelle, Leonardo F.; Cocchi, Luca; Harrison, Ben J.; Shavitt, Roseli G.; do Rosário, Maria Conceição; Ferrão, Ygor A.; de Mathis, Maria Alice; Cordioli, Aristides V.; Yücel, Murat; Pantelis, Christos; Mari, Jair de Jesus; Miguel, Euripedes C.; et al. (Elsevier, 2012)
We evaluated whether traumatic events are associated with a distinctive pattern of socio-demographic and clinical features of obsessive-compulsive disorder (OCD). We compared socio-demographic and clinical features of 106 patients developing OCD after post-traumatic stress disorder (PTSD; termed post-traumatic OCD), 41 patients developing OCD before PTSD (pre-traumatic OCD), and 810 OCD patients without any history of PTSD (non-traumatic OCD) using multinomial logistic regression analysis. A later age at onset of OCD, self-mutilation disorder, history of suicide plans, panic disorder with agoraphobia, and compulsive buying disorder were independently related to post-traumatic OCD. In contrast, earlier age at OCD onset, alcohol-related disorders, contamination-washing symptoms, and self-mutilation disorder were all independently associated with pre-traumatic OCD. In addition, patients with post-traumatic OCD without a previous history of obsessive-compulsive symptoms (OCS) showed lower educational levels, greater rates of contamination-washing symptoms, and more severe miscellaneous symptoms as compared to post-traumatic OCD patients with a history of OCS. © 2011 Elsevier Ltd.
Keywords: Comorbidity; Obsessive-compulsive disorder; Post-traumatic stress disorder; Traumatic life-events; Traumatic stress; adult; agoraphobia; alcohol abuse; automutilation; clinical feature; comorbidity; controlled study; disease classification; female; human; major clinical study; male; medical history; obsessive compulsive disorder; panic; posttraumatic stress disorder; suicide attempt; Adult; Compulsive Behavior; Female; Humans; Male; Middle Aged; Obsessive Behavior; Obsessive-Compulsive Disorder; Psychiatric Status Rating Scales; Severity of Illness Index; Stress Disorders, Post-Traumatic